HUKUM TINDAK PIDANA ILEGAL LOGGING KEBONHARJO JAWA TENGAH - Nanda Yuliska; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
The crime of illegal logging is one form of theft of state assets in the form of teak theft. In this study, it is explained whether the law enforcement of illegal logging crimes in the Kebonharjo Forest Management Unit, Rembang, Central Java has been implemented or not, along with the obstacles and efforts carried out by illegal logging law enforcement officers in the Kebonharjo forest management unit, Rembang, Central Java. Research using primary data sources by collecting data from literature studies. The process of law enforcement against illegal logging in forest management units includes preventive law enforcement, by empowering the community, improving environmental quality, establishing cooperation with relevant agencies and involving the community in law enforcement. Meanwhile, repressively provides administrative sanctions and criminal sanctions in the form of imprisonment, fines, imprisonment and compensation. The obstacles experienced by the Kebonharjo forest stakeholder unit came from internal aspects which included geographical factors, facilities and infrastructure, and the lack of personnel in the FMU, then from external aspects came from community factors, and legal sanctions factors. Implementation of Law Enforcement in Forest Management Units with obstacles originating from the internal and external aspects mentioned above that can be resolved by law enforcement in FMUs by increasing the ability and motivation of field officers, conducting socialization about Illegal Logging, and coordinating with agencies related activities, as well as empowering the community around the Kebonharjo KPH unit.